Perception of Non-Arabic Language Students on Arabic Language Courses at State Islamic Universities in Indonesia: Qualitative Research With NVivo Software Analysis - Abdul Karim; Duwi Purwati (Al-Muyassar: Journal of Arabic Education, 2026)
Arabic has a central position as the foundation of science and identity in Islamic higher education, especially in State Islamic Universities. This research aims to reveal the perception of non-Arab students towards the Arabic language courses required at the State Islamic University. With a qualitative-descriptive approach, data was collected through semi-structured interviews with students from three different study programs and analyzed using NVivo software. The results show that the majority of students realize the urgency of the Arabic language as the key to understanding Islamic literature, supporting academic competence, and being relevant to professional needs, such as sharia economics and basic education. However, learning Arabic is faced with methodological challenges (rigid teaching methods, lack of practice) and personal challenges (lack of initial experience, grammatical difficulties). Students develop self-paced (visual aids, online courses) and collaborative (group discussions, cross-disciplinary consultation) strategies to overcome these barriers. These findings emphasize the need for contextual, integrative, and practice-based curriculum innovation, as well as the use of learning technologies. With an adaptive approach, learning Arabic at the State Islamic University can become more meaningful and relevant, reinforcing the language's role as a bridge between the Islamic scientific tradition and the needs of the global era.